Room-temperature synthesis of nickel nanoparticles and their use as catalyst for methyl orange dye degradation. (2018) - Mondal, Arijit; Mukherjee, Debasmita; Mukherjee, Deb Kumar
We demonstrate here a simple and versatile route to prepare nickel nanoparticles from nickel sulphate using a surfactant and sodium borohydride as the reductant. These active and ordered structures of nickel nanoparticles were found to be efficient catalysts for degradation of methyl orange in aqueous medium. The particles remaining in solution were found to possess excellent catalytic activity even after several recycling attempts and have little propensity to coalesce or aggregate into inactive bigger lumps. Size selectivity was found to be one major reason of catalytic reusability using metal nanoclusters for similar dye degradation under identical reaction conditions.